Existence Theorems For a(u,v)-monotone of nonstandard Hemivariational Inequality - HASHOOSH, AYED ELEIWIS; M. Alimohammady, M. Alimohammady (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
In this paper, we consider the existence result of a nonstandard hemivariational inequalities with a(u,v) -monotone mapping in reflexive and non reflexive Banachs space. Finally, we provide sufficient conditions for which that inequality has a solution in the case of unbounded sets, via the fixed point and KKM theorems.